Doc Bushong (Symphony in the Flint Hills, 2012)
The naming and history of the little towns of Bushong and Comiskey; a legacy of the St. Louis Browns baseball team.
Keywords: Council Grove; Osage City; Ottawa Railroad; rail; Bushong; Lyon County; Missouri Pacific Railroad; Al " Doc" Bushong; Charlie Comiskey; Weeks Station; baseball; catcher; historical; game; sport; St. Louis Browns